2020
DOI: 10.2147/ott.s253474
|View full text |Cite
|
Sign up to set email alerts
|

<p>Downregulation of Hsa_circ_0000735 Inhibits the Proliferation, Migration, Invasion, and Glycolysis in Non-small-cell Lung Cancer by Targeting miR-940/BMPER Axis</p>

Abstract: Background: Lung cancer is the most commonly diagnosed cancer and the major cause of cancer-related deaths worldwide. The increasing studies have demonstrated that circular RNA (circRNA) was involved in the progression of various cancers, including non-smallcell lung cancer (NSCLC). This study was designed to assess the expression, roles and functional mechanisms of circ_0000735 in NSCLC. Materials and Methods: The expression levels of circ_0000735, miR-940 and bone morphogenetic protein binding endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Jiang et al demonstrated that miR-940 could inhibit cell invasion by targeting Snail in NSCLC (18). In addition, Huang et al reported that circ_0000735 modulated miR-940 to regulate BMPER expression (28). Indeed, this axis plays an important role in NSCLC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al demonstrated that miR-940 could inhibit cell invasion by targeting Snail in NSCLC (18). In addition, Huang et al reported that circ_0000735 modulated miR-940 to regulate BMPER expression (28). Indeed, this axis plays an important role in NSCLC progression.…”
Section: Discussionmentioning
confidence: 99%
“…The role of circRNAs in regulating glycolysis in cancer disease has been extensively studied in recent years [ 33 ]. For example, downregulation of circSEC31A or circ_0000735 can inhibit glycolytic metabolism in NSCLC cells [ 34 , 35 ]. In this study, knocking down circ_0078767 significantly promoted the proliferation, migration, and invasion of NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the deepening of circRNA research, researchers have found that the expression of circRNA is particularly important for the progression of many diseases, so it has great potential in the diagnosis and treatment of diseases. 21 , 22 In NSCLC, many circRNAs have been identified as potential biomarkers for NSCLC, such as circ_0000735, 23 circ_102179, 24 circ_103993, 25 and circ_0020123. 26 In previous studies, circ-PITX1 was found to be highly expressed in NSCLC and was related to NSCLC progression.…”
Section: Discussionmentioning
confidence: 99%